The 'trampoline ankle': severe medial malleolar physeal injuries in children and adolescents secondary to multioccupant use of trampolines. Issue 2 (March 2016) - Blumetti, Francesco C.; Gauthier, Luke; Moroz, Paul J.
Abstract : The purpose of this study was to describe a series of patients presenting with medial malleolus Salter–Harris types III and IV fractures (MacFarland fractures) related to trampoline use. In total, 11 patients were reviewed retrospectively (mean age: 11.8 years; four boys and seven girls). Salter–Harris type III fractures were more commonly seen ( n =7). Undisplaced fractures were more prevalent ( n =6). Six children underwent surgical treatment. Average follow-up time was 17.8 months. A medial physeal bar with subsequent growth arrest and ankle deformity was observed in two patients. More than one user was present on the trampoline at the time of the injury in nine of the reported cases. Medial malleolus growth-plate injuries can be seen after trampoline injuries where multiple users were involved. Potential complications including growth arrest can occur. Level of evidence: Level IV – case series.